PERENCANAAN PROSES PRODUKSI PENYABLONAN T-SHIRT DENGAN METODE AGGREGATE PLANNING HEURISTIK DI DOUBLEFIVE STORE AND CLOTHING YOGYAKARTA - Nugroho, Ius Adi; Emaputra, Andrean (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2021)
Aggreggate planning is a way to estimate the amount of output that will be produced to meet the demand obtained from forecasting for a period of more than 3 months or less than the next 18 months to meet demand in accordance with the company's overall production capacity to minimize the total costs incurred by the company. Doublefive Store and cloting is a company engaged in the online business by producing t-shirt printing. However, this company has not found a way to minimize the total cost of expenses. Therefore, research on aggregate planning is carried out to enable companies to arrange a way of optimally utilizing resources and supplies in order to achieve effective and efficient capacity which is based on future demand forecasts to minimize total expenditure costs. The method used is the heuristic method by calculating the workforce control planning and inventory control. Based on the research results, it is known that by using the labor control method, the costs incurred by the company are less than the inventory control method. The cost incurred based on the selected method is Rp. 20,442,987.22 with a difference of Rp. 10,025 from inventory control.